2021
DOI: 10.1016/j.intmar.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Brand-New Look at You: Predicting Brand Personality in Social Media Networks with Machine Learning

Abstract: Tools for analyzing social media text data to gain marketing insight have recently emerged. While a wealth of research has focused on automated human personality assessment, little research has focused on advancing methods for obtaining brand personality from social media content. Brand personality is a nuanced aspect of brands that has a consistent set of traits aside from its functional benefits. In this study, we introduce a novel, automated, and generalizable data analytics approach to extract near real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Like many empirical studies, ours has a weakness that could serve as a guiding source for further research on selfcongruity and brand passion. First, the analyses ignored one of the key dimensions in the research study of selfcongruity -"brand personality congruity" -as suggested by Pamuksuz et al (2021) and Shetty and Fitzsimmons (2021). Thus, future research should look at brand personality congruity as an indepen dent variable, with age and gender as moderating variables, to see how it affects service brand passion.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Like many empirical studies, ours has a weakness that could serve as a guiding source for further research on selfcongruity and brand passion. First, the analyses ignored one of the key dimensions in the research study of selfcongruity -"brand personality congruity" -as suggested by Pamuksuz et al (2021) and Shetty and Fitzsimmons (2021). Thus, future research should look at brand personality congruity as an indepen dent variable, with age and gender as moderating variables, to see how it affects service brand passion.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…KNN for regression is a popular algorithm that allows the prediction of the numerical target based on a similarity measure, which is often any distance function [73]. This technique is used in hybrid techniques or to compare performance, especially in predicting the influence on social networks [73], differences in the evaluation of products [77], and brand personality [78], among others.…”
Section: ) K-nearest Neighbor (Knn)mentioning
confidence: 99%
“…Additionally, the analysis investigated how negative feelings influence the market for firms [105] and the use and adoption of digital technologies and platforms for teleworking in the post-pandemic era [107]. In other social networks, the social influence and facilitating conditions directly impact the users' sentiments toward intelligent personal assistants (IPAs) [179], and studies also investigated estimates of love and loyalty for brands in Facebook photos [180] or prominent figures [78]. Moreover, other studies examined brand images on social networks (brand selfies) and user responses [52], how the media evaluates public agencies, particularly in low-trust contexts [104], and how narratives affect the effectiveness of influencers in sponsorship and likes and comments [181].…”
Section: E Text Analysis -Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Brand Personality is an effort for business actors or companies to add value to a brand from the outside in the eyes of consumers. This can be done through the experiences of other consumers, or it can be done by conducting marketing communications to introduce the product itself (Baştuğ et al, 2020;Koontz & Weihrich, 2015;Pamuksuz et al, 2021).…”
Section: B Brand Personalitymentioning
confidence: 99%